Spiritual Care Pada Pasien Hemodialisis: A Literature Review - Lalu Rodi Sanjaya; Sagiran Sagiran (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
One of the nursing interventions that can be used to overcome the psychological and health problems of hemodialysis patients is through spiritual care (SP).This article was prepared with the aim of providing literature on how to improve SP in hemodialysis patients. Article search uses the Proquest and Science Direct databases with a span of time (2016-2019) and JSTOR, in the time frame (2014-2019). The data search strategy uses English terms with keywords: Spiritual Care and Patient Hemodialysis and Literature Review.of the four articles reviewed, stated that religiosity or SP gave positive problems in depression, conflict, and stress in hemodialysis patients. In addition, it also increases social support and improves optimal health.SP is one of the nursing interventions that must be developed and considered to overcome psychological problems and to improve more optimal health